Technical measures for the rehabilitation in the hydrotechnical tunnel on Saska River - M. Kamenica - Zafirovski, Zlatko; Jovanovski, Milorad; Gacevski, Vasko (Association of structural engineers of Serbia, 2018)
Hydrotechnical tunnels represent challenging constructions from a design, construction and maintenance point of view. They are usually under constant effect of the water, which makes them prone to repairs and rehabilitation. The functionality of these kind of tunnels depends on the proper technical measures taken in their service period. This involves knowledge and experts from a few scientific areas. In this paper some of the technical measures for the rehabilitation of the hydrotechnical tunnel on Saska River are shown.
Keywords: Hydrotechnical tunnel; Analysis; Rehabilitation; PLAXIS 3D